The effects of nebivolol on intimal hyperplasia - Akar, I; Rahman, A; Burma, O; Ustundag, B; Uysal, A; Ozercan, IH; Ilkay, E (Medimond Publishing Co, 2005)
Intimal hyperplasia is a vascular remodelling process. In this study the 21 rabbits used were divided equally into 3 groups. The rabbits in control group only underwent balloon injury on abdominal aorta. The rabbits in solvent group and nebivolol group underwent balloon injury and they were treated with solvent and nebivolol intraperitoneally two days before injury and were continued for 28 days. At the end of the study, abdominal aortas were harvested and intimal-medial areas were measured. For endothelin-1, bFGF and PDGF-beta; sections were detected as immunohistologically. Tissue nitric oxide levels were measured. Nitric oxide levels were greater in nebivolol group than the other groups. The neointimal thickening and the immunstaining with endothelin-1, bFGF and PDGF-beta in nebivolol group is less than the other ones.
6th International Congress on Coronary Artery Disease -- OCT 29-NOV 01, 2005 -- Istanbul, TURKEY
Keywords: L-Arginine; Smooth-Muscle; Proliferation; Apoptosis; Injury; Rat